Gaining a Doctorate in Nursing in Chile: a path not without its difficulties (Revista Latino-Americana de Enfermagem, 2015)
;;OBJECTIVE:;; to analyze in detail the current situation of doctorate training in Nursing in Chile.;;;;METHODOLOGY:;; through a historical and contextual analysis of the background to the development of postgraduate education in Nursing, especially at doctorate level.;;;;RESULTS:;; aspects that limit development were identified in national institutionalism of the sciences as well as in higher education and health institutions, especially the limited value placed on nursing as an area of knowledge in this country, the lack of clear institutional policies for postgraduate studies, as well as the postgraduate's re-inclusion into the academic and care area, with access to national research funds difficult.;;;;FINAL CONSIDERATIONS:;; access to grants and funds, together with recognition as an area of knowledge belonging on academic schedules, especially in health institutions, are the main challenges to consolidation. One aspect that would enable a more rapid advance is through national and international inter-institutional agreements, adding together potential, with access to funds for studies and academic and student internships, enabling joint research to go ahead.;;